The tumor microenvironment disarms CD8+ T lymphocyte function via a miR-26a-EZH2 axis. (1st December 2016) - Long, Haixia; Xiang, Tong; Luo, Jing; Li, Fei; Lin, Regina; Liu, Siqi; Jiang, Shan; Hu, Chunyan; Chen, Gang; Wong, Elizabeth; Wan, Ying; Li, Qi-Jing; et al.
ABSTRACT: One of the most important factors that limit the potency of CD8 + cytotoxic T lymphocyte (CTL) responses is the tumor microenvironment (TME). Here, we provide evidence that miR-26a is a negative regulator of CTL function in the TME. Specifically, we identified miR-26a as a crucial suppressor gene in CTLs from the TME, as we found that, miR-26a expression was elevated in CTLs to respond to TME secretome stimulation. CTLs from miR-26a-transgenic mice showed impaired IFNγ and granzyme B production in response to their cognate antigen. Conversely, we found that miR-26a inhibition in CTLs could effectively increase the cytotoxicity and suppress tumor growth. Mechanically, we identified EZH2 as a direct target of miR-26a. miR-26a and EZH2 expression were found to be inversely correlated in CTLs, and the inhibition of EZH2 in CTLs impairs CTL function. These functional correlations were validated in a cohort of non-small cell lung cancer patients, indicating that the miR-26a-EZH2 axis is clinically relevant. Our findings suggested that miR-26a silencing as a novel strategy to improve the efficacy of CTL-based cancer immunotherapy.